The impact of social class and ability group on students academic achievement : a case study of primary schools in North Sumatra Province, Indonesia : a proposed framework for improvement - Siti Salmah (Kulliyyah of Education, International Islamic University Malaysia, 2021)
Ability group system (AGS) can be understood as grouping students according to their academic abilities. There are pros and cons of the ability group implementation in schools. This system is still practised in modern national educational systems, and Indonesia is among such countries. The present study explored the impact of students’ socioeconomic status (SES) and the AGS implementation on selected primary students’ academic achievement in the North Sumatra Province of Indonesia. The research utilised the qualitative method and followed a case study design confined to a selected primary school that implemented the ability group system in their teaching and learning process. A total of 12 informants were selected using the purposive sampling technique. The sample consisted of four teachers with experience adopting ability groups in the teaching and learning process and eight parents who have children in different ability level classes. Data was obtained using semi-structured interviews, non-participant classroom observation, and document analysis. The findings suggest that ability group implementation in the North Sumatra Province of Indonesia has widened the academic gap among students of different social classes. Students placed in high ability groups benefited more from AGS than students placed in low ability groups in terms of learning duration, quality of teaching and learning, and care, which is reflected in the academic achievement of all ability groups. The teachers believed that there are advantages and disadvantages to ability group implementation. They showed a varied attitude towards it, with some of them in favour of the system while others rejected it. The findings demonstrate that SES background and AGS could impact students’ academic performance. Teachers who lack the competence and the training in the teaching and learning process for AGS will face challenges regarding the system. Parents with children in high ability classes were supportive of the ability group while the rest believed that students should study in heterogeneous ability classes. Overall, most of the parents agreed that SES could impact their children’ academic achievement. Therefore, the findings provide an invaluable resource for designing a proposed framework for ability group implementations. This framework would be a step forward in ensuring equal learning opportunities and benefits for students of all ability groups. Besides, the research finding gathers empirical evidence about the issue related to ability group implementation. Also, this contributed to the analysis provided by the conflict paradigm in general and the critical theory in particular regarding the relationship between social class and educational attainment, especially the application of ‘ability group.’